Social principles of emancipatory agroecologies - Giraldo, Omar Felipe; Rosset, Peter Michael [UNESP] (Universidade Federal do Paraná, 2021)
In this article we critique the attempts to institutionalize agroecology, which we contrast with the social processes of social movements. We argue that the way of working of popular or peoples' agroecology is very different from the logic with which public policies, programs and projects are being designed by governments, international organizations and non-governmental organizations, which we classify here, according to their political orientation, as neoliberal or reformist. We show the radical political, economic, organizational, methodological, pedagogical and philosophical difference between these false agroecologies and emancipatory agroecologies. From this divergence we propose six principles for building truly transformative and revolutionary agroecological processes: 1) questioning and transforming structures, not reproducing them; 2) shaping economies based on use value, not change value; 3) strengthening organicity and thinking in terms of collective processes, not individualized projects; 4) building horizontal processes, not hierarchies; 5) building capacity to struggle and transform, not to conform; and 6) acting based on culture and spirituality, not on productivism.
Principios sociales de las agroecologías emancipadoras
Keywords: Agroecology; Autonomy; Cooptation; Post-development